PENGARUH PUPUK ORGANIK CAIR (POC) DENGAN MOL TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN SAWI PAKCOY (Brassica rap L.) - Dita Aulia, Dita Aulia; Masfianis Rahayu, Alfickril; Setyawati, Harimbi (jurnal ATMOSPHERE, 2022)
Liquid organic fertilizer (POC) is a solution resulting from the decomposition of organic matter containing more than one nutrient element, namely N, P, and K. Fertilizer plays an important role in increasing crop yields, especially in soils with low nutrient content. In this study, 2 planting media were used, namely packaged planting media and planting media taken from agricultural land in Batu City which utilized liquid organic fertilizer (POC) from vegetable waste using local microorganism bioactivators with the aim of determining the effect of POC doses from vegetable waste on growth and production. mustard plants of 10 mL, 15 mL, 20 mL, 25 mL, and 30 mL. The best growth of pakcoy mustard plants using the Batu agricultural land planting medium was the best at doses of 25 mL and 30 mL. Meanwhile, the growth of mustard greens using packaged planting media this time cannot be ascertained at what dose the best mustard greens are, because in this planting medium many samples in polybags died and grew abnormally. Caused by damage to the leaves caused by pests that attack.